Adsorptive Removal of Malachite Green Dye from Aqueous Solution Using Chemically Modified Charred and Xanthated Wheat Bran - Dhami, Dilli; Homagai, Puspa Lal (Journal of Nepal Chemical Society, 2020)
Adsorptive removal of Malachite Green (MB) dye from aqueous solution using chemically modified Wheat Bran has been investigated. Wheat bran was chemically modified to charred through charring process and it was further modified to xanthated through xanthation process. Batch experiments were carried out to study the experimental parameters such as effect of pH, effect of concentration and effect of contact time for both Charred Wheat Bran (CWB) and Xanthated Wheat Bran (XWB) simultaneously. The concentrations of dye ions before and after the adsorption were determined by using UV-Visible Spectrophotometer. The dye uptake was maximum for the initial pH of 4 for both CWB and XWB but the percentage removal for XWB was found to be effective in comparison with CWB i.e., 98.45% and 93.45% respectively with adsorbent dose of 0.025g and agitation speed of 190 rpm. The applicability of Langmuir isotherm was tested. The adsorption capacity of MG dye into CWB and XWB was found to be 69 mg/g and 112.9 mg/g, respectively. Similarly, the kinetic data best fitted for pseudo-second order. Hence, the result showed that XWB may be an attractive alternative for the removal of MG dye from aqueous solution in comparison to CWB as bio-adsorbent.